COURSES IN THE FIELD OF CIVIL AVIATION SECURITY - Piotr UCHROŃSKI (Scientific Journal of Silesian University of Technology. Series Transport)
Polish accession to the EU and which consequently adapt Polish law to EU standards drew attention to the aviation community on the need for training and improvement of the quality of work people employed at the airport. Similarly, the subject was developed in the protection of civil aviation. Here, however, the direct stimulus for the formation of all kinds of regulations were the events in the USA 11.09.2001 r. It was then that apart from the obvious need to introduce more restrictive rules related to the security control of passengers and their luggage, it was also noted for staff training, their skills, threat detection and appropriate response to all types of custom passenger behavior. Then also placed special emphasis on quality control work, which is reflected in even the National Training Programme and the National Quality Control Programme, which are designed, on the one hand, professional prepare of the screeners for the implementation of the their statutory tasks, on the other hand, has created a tool to supervise the quality of the work done by this group of workers. Awareness of the human factor as an element that could significantly affect the level of airport security makes this factor is particularly treated in the protection of civil aviation. The consequences of human error, resulting from an act of conscious or unintentional, may in fact be catastrophic for the airport, the carrier and passengers.